Estudio serológico de Leucosis Enzoótica Bovina su relación a parámetros reproductivos - Mena Viera, Maritza Lizeth (2017)
Enzootic Bovine Leukosis (EBL) it is a disease caused by a retrovirus that affects the bovine species. This disease has an important impact in the world, and its prevalence varies from region to region. In Ecuador, a frequency ranging from 7% to 65% have been reported. In the same way, the lack of an effective treatment, indefinite permanence of the virus in the affected animals. For the alternative control was to determine by means of serology the Enzootic Bovine Leukosis Virus and its relation with the reproductive parameters. In total were 40 female animals selected, distributed in 20 cero positive and 20 cero negative a (VLBE). Two blood samples were collected from the selected cows by puncture of the middle coccygeal vein with the use of Vacutainer® red cap tube vacuette® for serological diagnosis of VLBE and lila vacuette® capillary tubes for hematic biometry. The 40 animals were distributed into two groups; a control group and an experimental group one. The experimental group (T1) it did not present a significant difference on the relation of the serological status to the VLBE in relation to the reproductive parameters that were analyzed giving a value of (p> 0.05). Also, there were not significant differences regarding the different red blood cell parameters of T1 (p> 0.05). As for the white series, in lymphocytes and monocytes there were significant differences between the control groups (positive and negative). In conclusion, this study does not provide conclusive data on the relationship of the serological status to the VLBE in relation to the reproductive parameters analyzed in the bovines, although it was possible to verify some important relation with the interval between deliveries, services by conception, open days and reproductive status; In addition, although there was no statistical significance in many of the differences found, cero negative animals showed better indicators than seropositive animals. In addition, it was observed that the white series (lymphocytes and monocytes), generated an immunological niche of stability to the disease.